Pengaruh Fasilitas Kerja, Lingkungan kerja Dan Kepuasan Kerja Terhadap Turnover Intention pada Karyawan Produksi PT Intim Harmonis Food Sukorejo: (Studi pada Karyawan Produksi PT Intim Harmonis Food Sukorejo) - M. Dardiri; M. Sulhan (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
Dardiri. Business Administration Study Program, Yudharta University Pasuruan. July 2023. The effect of work facilities, work environment, and job satisfaction on study turnover intention of production employees of PT. Intimate Harmonic Food Sukorejo This study aims to determine the effect of work facilities, work environment, and job satisfaction on turnover intention in production employees at PT. Intimate Harmonic Food Sukorejo. This type of research is a quantitative research. The population in this study are production employees throughout PT. Intimate Harmonic food Sukorejo, the sample of this research is 150 Respondents. The data source in this research is primary data source. Data collection techniques using a questionnaire. The data analysis tool used is multiple linear regression analysis with the help of SPPS 24 software. The results of this study show (1). Work facilities have a significant effect on turnover intention. (2). The work environment has a significant effect on turnover intention. (3). Satisfaction has a significant effect on turnover intention. (4). work facilities, work environment and job satisfaction simultaneously influence turnover intention